Extended Time in the Digital Environment (Papers in Arts and Humanities, 2022)
Several aspects of human life have been extended through the digital environment: programs and apps help to expand cognitive capacity of human brain, drives and memories of ICT devices as well as cloud services provide an external memory storage for human remembrance, portable devices serve as multiple communication supply including text, voice, and video channels, social networking sites offer extensions for social life – and this development is in continual expanse. Nevertheless, time is also involved in this process. On the one hand, the relativity of time is obvious since the technological development transformed not only the sense of time but the culturally or traditionally determined frames of time itself. On the other hand, extended parts of human life can have an independent existence: regardless of time, regardless of human life they can subsist long after the death of the person. In other words, digital environment provides the possibility to extend the time for humanity. Is this extension a device for eternal life, or at least for a longer lifespan? Will this extension transform our thinking about time – or about our life?
Keywords: digital environment; extension of human capacities; web 2.0; brain emulation; electronic civilization